Fortifying the city of Salvador: municipal constraint or ‘informal imposition’? State-building and long-distance governance in early 17th century Brazil (c. 1604) - Vicente Martín, Irene María (Anais de História de Além-Mar, 2019)
Resumo disponível no PDF